A difficult dialogue between hagiography and iconography - Carletti, Emanuele,Massoni, Marco (Ikon;Rijeka, 2021;Band 14 (2021), Seite 153-164, 2021)
In 1888, Leo XIII canonised the founders of the Servite Order. For the first time the founder of a religious community was not recognised in a single figure but in a group of confessors. They were canonized six centuries after the Order’s foundation and this process required considerable efforts. The paper deals with the Servite hagiography and the Founders’ iconography, examining intersections and relationships between them from the 14th century up to 1570. The process of transmission of the Founders’ memory was extremely problematic because of the contradictions that marked the group ever since the hermit experience on Mount Senario in the 1240s-1250s. The memory of the origins that has been transmitted to us was written in a completely changed context, when the Order was already formed as mendicant, promoting other blessed friars’ figures, above all Philip of Florence. In this context, the Founders were largely overlooked, as can be seen in few surviving 13th and 14th-centuries hagiographies, such as the Legenda de origine Ordinis or the Legenda beati Philippi, as well as from the absence of figurative representations. From the 17th century, due to the opening of the canonization process, the Founders’ memory underwent a careful review. For this purpose, in the printed Positiones and in the handwritten reports, some medieval-supposed artworks, portraying the Founders, were described. This text explains how the iconographic elaboration in 17th and 18th centuries is the result of a peculiar interpretation of the hagiographic sources of previous centuries, and how this operation was so successful that it led to the canonization of a group of the seven individuals.
Keywords: Ordensgründer; Hagiografie; Heiligenvita; Heiligenbild